2021
DOI: 10.1002/pc.26433
|View full text |Cite
|
Sign up to set email alerts
|

Research on mechanical and erosion behavior of stepped polymeric functionally graded materials reinforced with aluminum

Abstract: The aim of this research is to evaluate the mechanical and erosion characteristics of stepped polymeric functionally graded materials (PFGMs) reinforced with aluminum particles. By varying the filler content, gradation is achieved along the sample's thickness direction. Three distinct methodologies were adopted in the fabrication of PFGMs; no curing time between the layers (M1), providing curing time between the layers at room temperature (M2) and thermal curing between the layers at 60 C (M3). The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Therefore, it is critical to have better understanding of erosion wear phenomenon of polymer composite materials. Over the past decade, the researchers utilized different conventional metal [ 1 ] and ceramic materials as reinforcements for development of high wear resistant composite materials. Though conventional materials have established their competence in sustaining wear some of the drawbacks like high self‐weight, cost and non‐renewable made researchers to choose polymer composites which have high specific and strength inherent lubricant properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is critical to have better understanding of erosion wear phenomenon of polymer composite materials. Over the past decade, the researchers utilized different conventional metal [ 1 ] and ceramic materials as reinforcements for development of high wear resistant composite materials. Though conventional materials have established their competence in sustaining wear some of the drawbacks like high self‐weight, cost and non‐renewable made researchers to choose polymer composites which have high specific and strength inherent lubricant properties.…”
Section: Introductionmentioning
confidence: 99%
“…30 Mechanical and erosive behavior of stepped polymeric functionally graded materials reinforced with aluminum was studied and it was found that by varying the filler content, gradation is achieved along the sample's thickness direction. 31 Comparing the sliding wear behavior of 10 wt% SiC particle-reinforced aluminum matrix composite (AMC) with that of cenosphere-filled aluminum syntactic foam (ASF), the research has been done. It was discovered that, in both dry and lubricated settings, ASF exhibits lower coefficients of friction, wear rates, and temperature increases than AMC.…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered that the craters on the specimen surface caused by the presence of cenosphere play a significant role in the wear process after studying the dry sliding wear behavior of cenosphere‐reinforced aluminum syntactic foam 30 . Mechanical and erosive behavior of stepped polymeric functionally graded materials reinforced with aluminum was studied and it was found that by varying the filler content, gradation is achieved along the sample's thickness direction 31 . Comparing the sliding wear behavior of 10 wt% SiC particle‐reinforced aluminum matrix composite (AMC) with that of cenosphere‐filled aluminum syntactic foam (ASF), the research has been done.…”
Section: Introductionmentioning
confidence: 99%
“…These materials can be fabricated using powder metallurgy (PM), additive manufacturing, vapor deposition, centrifugal casting, and so on. 5,6 Among the processes, PM is widely used to develop metal–metal FGMs owing to its fabrication ease and ability to produce complex geometries. PM includes mixing of metal powders and compression in a mold followed by sintering and cooling in a furnace.…”
Section: Introductionmentioning
confidence: 99%